Prosistas de la República (Biblioteca Ecuatoriana Mínima. La Colonia y la República, 1960)
Contiene: Fray Vicente Solano, Benigno Malo, Francisco Javier Salazar, Antonio Flores, Roberto Espinosa, Francisco Febres Cordero (Hno. Miguel), Honorato Vázquez, Federico Proaño, Alberto Muñoz Vernaza